Empowering Vocational Education Teachers with Digital Competencies for 21" Century Learning (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This article focuses on the empowerment of vocational education teachers with digital competencies for 21st century learning. In today's rapidly changing digital landscape, it is crucial that vocational education teachers possess the necessary skills to prepare students for the workforce. This article discusses the importance of digital competencies in vocational education and examines the current state of these competencies among  teachers. Key digital competencies that vocational education teachers need to possess are identified, and strategies for empowering them with these competencies are presented. The article also highlights the challenges and barriers that may hinder the implementation  of digital competencies in vocational education and provides case studies of successful implementation. Finally, the article concludes with future directions and recommendations for empowering vocational education teachers with digital competencies to prepare students for the 21" century workforce.